The global epidemic of chronic kidney disease - Davids, M.R. (SA Heart Journal, 2017)
Chronic kidney disease (CKD) is defined as kidney damage or a glomerular filtration rate (GFR) of < 60 ml/min/1.73 m2 for 3 months or more. About one adult in ten, or over 500 million people worldwide, are affected, with diabetic nephropathy, glomerulonephritis and uncontrolled hypertension being the major causes. The global burden of CKD is expected to increase in parallel with the increase in diabetes, with the developing world bearing the brunt of this epidemic. The major consequences of CKD are the development of end-stage renal disease (ESRD) and, even more frequently, premature death from cardiovascular disease. This results from a markedly increased prevalence as well as a higher case fatality rate. CKD is increasingly being recognised as a very strong risk factor for cardiovascular disease, justifying lower targets for blood pressure and lipid control. Apart from the frequent presence of “traditional” risk factors, these patients often suffer from “nontraditional” factors such as hyperphosphataemia, hyperhomocystinaemia, malnutrition, chronic fluid overload and anaemia. The management of ESRD is extremely costly, and it is therefore not surprising that most patients on treatment are to be found in high income countries. In many African countries there is little or no treatment available. The focus has therefore turned to the early detection and treatment of CKD to prevent progression to ESRD and to decrease the morbidity and mortality from cardiovascular disease. Several international initiatives have been launched in response to this global public health problem.